Knowledge and Attitudes of Dentists Regarding the Etiology and Management of Non-Carious Cervical Lesions in teeth - Feili, Fahimeh; Seidkhani, Hossein; Mahdavi, Mohammad Hossein (Journal of Dental School, 2025)
Objective(s): This study aimed to assess the knowledge and attitudes of dentists regarding the etiology and management of non-carious cervical lesions (NCCLs) and to identify gaps in their understanding. Methods: A cross-sectional study was conducted involving 119 general dentists in Ilam, Iran. A validated questionnaire, consisting of 39 questions concerning the etiology and management of NCCLs, was distributed. Data were analyzed using descriptive and inferential statistical methods by Chi-square and T-test at p<0.05. Results: There was significant difference in knowledge and attitude based on age and experience. Dentists over 40 and those with over 10 years of experience displayed greater knowledge and attitude regarding the etiology and management of NCCLs (P < 0.01). However, no significant differences were observed between the two genders. Conclusion: Findings highlight a critical need for continuing education among dentists, particularly for younger practitioners. Enhancing knowledge and attitudes towards NCCLs can improve clinical practices and patient outcomes. Targeted educational programs are recommended to address the identified gaps in understanding and management strategies for NCCLs.